Direct optical excitation of two and three magnons in a-Fe2O3 - Tanabe, Y.; Fujimaki, Y.; Kojima, K.; Uchida, S.; Onari, S.; Matsuo, T.; Azuma, S.; Hanamura, E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
Direct excitation of two and three magnons is observed in midinfrared absorption and Raman scattering spectra of a-Fe2O3 crystals. These polarization characteristics and the spectra themselves are shown to be understood from group-theoretical point of view. The microscopic mechanism of three-magnon excitation is proposed in addition to that of well-known two-magnon excitation process.